Model dan Proses Komunikasi - Efendi, Erwan; Valentiyo, Aprillian; Zahra, Aqila; Yani, Inda; Farhan, Muhammad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Communication is very necessary for interaction between humans, therefore communication cannot be separated from everyday life, so that without communication, human life will not run perfectly. Because communication has a very important role, a communication model was created. Communication has several models, and each model has a different definition. The communication model was created to make it easier to understand the communication process and see the basic components that need to be present in a communication. Communication is also a process, this can be seen from every symptom or event that cannot be separated from the communication that exists between humans